1977
DOI: 10.1039/dt9770001328
|View full text |Cite
|
Sign up to set email alerts
|

1,1,2,2,2,2,3,3,3,3-Decacarbonyl-1-(η-cyclohexa-1,3-diene)-triangulo-triosmium: a novel intermediate in synthetic osmium cluster chemistry

Abstract: DecacurbonyZ-l-(~-cyelo~exa-1,3-diene)-triangulo-triosnziunz, [Os,(CO) ,,(C,H,>] (1) .-The compound [Os3(CO),,H,] (500 mg) was added to distilled refluxing n-hexane containing an excess of cyclohexa-1,3-diene or -1,4-diene under nitrogen. After 4 h, the solvent and excess diene were removed in vacuo and the 4 residue was chromatographed on silica plates using hexanediethyl ether (19 : 1) as eluant. The required compound was removed from the plates as an intense orange band and was recrystallized from hexane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 0 publications
0
56
0
2
Order By: Relevance
“…It is also worth noting that the substrates cope of such compounds includes molecules such as ammonia,which hashistorically provendifficult to activate using precious metalc atalysts due to the unfavourable coordination/activation equilibrium. Newr outes resultingi nt he activation of NÀHb onds in ammonia are particularly appealing, becauseo ft he dearth of transition-metal systems capable of effecting such at ransformation, [7][8][9][10][11][12][13][14][15][16][17][18][19] and the relevance of NÀHa ctivation to an umber of potentially important industrialp rocesses. [20] More recently,g eometrically constrained compounds based on phosphorus(III) have also received significant attention in this field.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that the substrates cope of such compounds includes molecules such as ammonia,which hashistorically provendifficult to activate using precious metalc atalysts due to the unfavourable coordination/activation equilibrium. Newr outes resultingi nt he activation of NÀHb onds in ammonia are particularly appealing, becauseo ft he dearth of transition-metal systems capable of effecting such at ransformation, [7][8][9][10][11][12][13][14][15][16][17][18][19] and the relevance of NÀHa ctivation to an umber of potentially important industrialp rocesses. [20] More recently,g eometrically constrained compounds based on phosphorus(III) have also received significant attention in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the diene complexes Os 3 (CO) 10 (g 4 -cyclohexadiene) [13] and Os 3 (CO) 10 (g 4 -norbornadiene) [11] were prepared in a same reaction fashion, while Os 3 (CO) 10 (g 4 -butadiene) was obtained by treating H 2 Os 3 (CO) 10 with excess butadiene [9]. Although the isolation of 1 was mentioned [10], no spectroscopic data have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…It turns out that Os 3 (CO) 11 (NCMe) and Os 3 (CO) 10 (NCMe) 2 are among the most valuable reagents for the synthesis of a wealth of new triosmium cluster complexes. Shapley and co-workers [9][10][11], and Lewis and co-workers [12,13] have previously studied the reactions of H 2 Os 3 (CO) 10 and Os 3 (CO) 10 (NCMe) 2 with a variety of conjugated dienes. In this paper, we wish to report the synthesis of Os 3 (CO) 10 (g 4 -C 8 H 12 ) (1), which contains a non-conjugated 1,5-cyclooctadiene ligand, from Os 3 (CO) 10 (NCMe) 2 and its reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[8] New routes resulting in the activation of NÀHb onds in ammonia are particularly appealing because of the dearth of transition-metal systems capable of effecting such atransformation [9][10][11][12][13][14][15][16][17][18][19][20][21] and the relevance of N À H activation to an umber of potentially important industrial processes. [22] In addition to these high profile examples,r ecent studies have shown that complexes of phosphorus(III) with distorted geometry can cleave arange of polarized EÀHbonds (E=Oor N).…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Therefore,a dvances in main group mediated activation of ammonia are of great interest. [4, 5, 6c-d,24, 26, 27, 30-32] Ther eaction of 1 with ammonia gas (1 atm) results in the quantitative conversion of 1 to anew product, 2 (Scheme 2).…”
mentioning
confidence: 99%